Investigation of the boundary-valued problem on resonance MHD non-uniformity by integral equations using - Oleksandrov, Y.N.; Nevliudov, I.Sh.; Chala, O.O.; Botsman, I.B.; Nevliudova, V.V. (Вопросы атомной науки и техники, 2021)
Numerical simulation of interior field velocity is studied on the basis of the rigorous analytical solution of the boundary-valued magnetohydrodynamics problem on the sphere type non-uniformities. The basis for the analytical solution is the method of integral equations of linear magnetohydrodynamics. The analysis of the obtained results is carried out. Проведено чисельне моделювання швидкості внутрішнього поля для МГД-неоднорідності на основі точно аналітичного рішення крайової задачі магнітогідродинаміки. В основі аналітичного рішення лежить метод інтегральних рівнянь лінійної магнітогідродинаміки. Проведено аналіз отриманих результатів. Проведено численное моделирование скорости внутреннего поля для МГД-неоднородности на основе строго аналитического решения краевой задачи магнитогидродинамики. В основе аналитического решения лежит метод интегральных уравнений линейной магнитогидродинамики. Проведен анализ полученных результатов.